The Mental Image of a Product and its Influence on Purchase and Repeat Purchase Decisions by Saudi Consumers - Fait, Adil Mohamed Ahmed (Edelweiss Applied Science and Technology, 2025)
This study examines how product aesthetics, self-image congruence, perceived quality, and exposure to advertising collectively contribute to consumer perception and drive purchasing behavior among Saudi consumers. Grounded in Consumer Perception Theory (CPT) and Self-Congruity Theory (SCT), the study employs quantitative research on data collected from 871 respondents. The findings indicate that product aesthetics and perceived quality strongly influence purchasing decisions, while self-image congruence and exposure to advertising play significant but secondary roles. Furthermore, purchasing decisions mediate the relationship between these independent variables and repeat purchase behavior, reinforcing the importance of a product’s mental image in fostering long-term consumer loyalty. The study offers practical insights for marketers, emphasizing the need for brands to align their design, quality, and promotional efforts with consumer expectations and cultural values in the Saudi market. Future research should explore longitudinal impacts and the impact of external factors, such as technological advancements and market competition, on product perception and consumer loyalty.